The Construction of KH. Ahmad Mustofa Bisri’s Oral Exegesis: A Conceptual Framework - Muhammad Irsad (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Studies of Qur'anic interpretation in academic tradition generally focus on written interpretations, while oral exegesis, despite their significance in religious practice, are still relatively rarely studied systematically. Oral exegesis are communicative, situational, and contextual in nature, requiring separate analysis to understand their structure and dynamics. This study aims to formulate Gus Mus’s oral exegesis through a conceptual approach that combines the context of delivery, interpretation structure, reference sources, and interpretation strategies. This study uses a qualitative method with a descriptive-analytical design through thematic analysis of oral exegesis, which is operationalized through a process of transcription, open coding, categorization, and identification of interpretive patterns and themes. The research data consists of transcripts sourced from recordings of Gus Mus’s al-Ibrīz interpretation lectures, collected through audio-visual documentation and other relevant supporting sources. The results of the study show that Gus Mus’s oral exegesis is constructed through a complex analysis method, in which the text of the Qur'an, scholarly tradition, the interpreter's historical experience, and the socio-cultural context of the audience interact simultaneously. Intratextual and intertextual approaches strengthen the coherence and legitimacy of meaning, while the dimensions of locality, affirmative and critical commentary, and recontextualization ensure relevance and effective communication with the audience. The findings of this study offer a new conceptual framework in the study of oral exegesis, enriching contemporary Qur'anic interpretation studies and opening up opportunities for further research on the oral exegesis practices of other figures and written interpretations.